Architecture of Syllables in Lattakian Syrian Arabic - Shaheen , Buthaina (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper provides a description of syllable structure in Lattakian Syrian Arabic. Results of a study conducted for this purpose revealed 14 basic syllable structures. It also illuminates the characteristics of syllable elements in this dialect. Some parameters, namely, the minimum sonority distance and the obligatory contour principle were investigated.